Analysis of the functional state of students in the process of healthy training exercises in different phases of the ovarian-menstrual cycle - N.V. Petrenko; O.P. Petrenko; V.B. Romanova; V.V. Ostapenko (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Aim: to substantiate the application of a rational program of health-training sessions in the educational process of physical education of students in different phases of the ovarian-menstrual cycle. Material: in study participated students (n=127), who did not have deviations in health (the main medical group). According to the results of the tests were determined: heart rate; blood pressure; vital capacity of the lungs. To determine physical performance was used Harvard step-test. Physical exercises from the main means of health fitness were used differentially and dosed. Results: It was established that the consideration in the phases of the ovarian-menstrual cycle of indicators of the functional state, changes in well-being and working capacity give an opportunity: planning loads in the training process; adjustment of volume and intensity of loads. We recommend to schedule the load of our program as follows: in the menstrual phase - the development of flexibility (moderate load); in the postmenstrual phase - development of coordination, overall endurance; in ovulatory - speed development; in postovulatory - development of special endurance; in premenstrual - the development of strength, flexibility. In the postmenstrual and postovulatory phase, a high level of physical working capacity, functional state of the cardiopulmonary system has been registered. It also has a positive effect on body weight correction in the women students. Conclusions: When developing programs of health training sessions with women students it is necessary to take into account the phases of the ovarian-menstrual cycle.